Dampened inflammatory signalling and myeloid-derived suppressor-like cell accumulation reduces circulating monocytic HLA-DR density and may associate with malignancy risk in long-term renal transplant recipients - Bottomley, MJ; Harden, PN; Wood, KJ; Hester, J; Issa, F (Frontiers Media SA, 2022)
Background: Malignancy is a major cause of morbidity and mortality in transplant recipients. Identification of those at highest risk could facilitate pre-emptive intervention such as reduction of immunosuppression. Reduced circulating monocytic HLA-DR density is a marker of immune depression in the general population and associates with poorer outcome in critical illness. It has recently been used as a safety marker in adoptive cell therapy trials in renal transplantation. Despite its potential as a marker of dampened immune responses, factors that impact upon monocytic HLA-DR density and the long-term clinical sequelae of this have not been assessed in transplant recipients.